Pandangan Masyarakat Indonesia Terhadap Budaya Korea Selatan: Studi Kasus Manhwa Noblesse pada Aplikasi Line Webtoon - Nadia Istiani Zagita; Rudi Sukandar (COMMENTATE: Journal of Communication Management, 2021)
Line Webtoon is one of the media used by South Korea in spreading Hallyu Wave. It has driven the views or opinions of the South Korean culture through manhwa (Korean Comic) called â€œNoblesseâ€ in the application Line Webtoon using Comic Theory from Scott McCloud. The analysis of case studies on the Noblesse manhwa showed that opinions were presented and exhanged related to the characters, the messages being conveyed, and reader's expectations about in the manhwa. The readers' enthusiasm for this manhwa has made Noblesse one of the most favored manhwas. The implications of this research led to the intercultural communication associated with the comic elements in this manhwa.